THE EXTERNAL INTERNATIONAL PEERS ASSESSORS OF THE QUALITY OF THE EDUCATIONAL SERVICE OF THE UNIVERSITY INSTITUTIONS - Gutiérrez Huby, Ana María (2009)
The goal of this article is to offer a further scope with regard to the external peer evaluators and to emphasize the relevance of their action within a process of institutional accreditation. In this framework it was considered as paragraphs, their mission, their criterion, their abilities and skills in the area of action, their role as a part in the accreditation organization, among other interesting aspects to have in consideration facing- with a range of possibilities- an external evaluation. Approaching the topic implied the research of documentary material published by well-known Latin-American accreditation entities that draw upon the collaboration of work teams in order to technically validate the educational service that is provided by the evaluated programs, as well as university institutions that experienced previous processes of accreditation. The resulting conclusion is then, the consideration of the suitable profile that these specialists must maintain to be considered as such.